Improved corrosion resistance of commercially pure magnesium after its modification by plasma electrolytic oxidation with organic additives (2018)
The optimal mechanical properties render magnesium widely used in industrial and biomedical applications. However, magnesium is highly reactive and unstable in aqueous solutions, which can be modulated to increase stability of reactive metals that include the use of alloys or by altering the surface with coatings. Plasma electrolytic oxidation is an efficient and tuneable method to apply a surface coating. By varying the plasma electrolytic oxidation parameters voltage, current density, time and (additives in the) electrolytic solution, the morphology, composition and surface energy of surface coatings are set. In the present study, we evaluated the influence on surface coatings of two solute additives, i.e. hexamethylenetetramine and mannitol, to base solutes silicate and potassium hydroxide. Results from in vitro studies in NaCl demonstrated an improvement in the corrosion resistance. In addition, coatings were obtained by a two-step anodization procedure, firstly anodizing in an electrolyte solution containing sodium fluoride and secondly in an electrolyte solution with hexamethylenetetramine and mannitol, respectively. Results showed that the first layer acts as a protective layer which improves the corrosion resistance in comparison with the samples with a single anodizing step. In conclusion, these coatings are promising candidates to be used in biomedical applications in particular because the components are non-toxic for the body and the rate of degradation of the surface coating is lower than that of pure magnesium.